A rare case of Ewing's sarcoma in a 4-year-old child treated by tumor endoprosthetics using 3D printing - Vladimir Stavrev; Luben Stokov; Petko Ganev; Georgi Georgiev (Journal of the Bulgarian Orthopaedics and Trauma Association)
Orthopedic oncology surgery often requires, by its very nature, precise and often extensive resections of bone and soft tissue involved in or near the tumor mass.